Risk factors for a marked decline in anti-Müllerian hormone after minimally invasive ovarian cystectomy - Eun Bi Jang; Yoon Sun Kook; A. Jin Lee; Seung-Hyuk Shim; Sun Joo Lee; Tae Jin Kim; Kyeong A. So (Medicine, 2026)
This study aimed to investigate the factors affecting the decline of serum anti-Müllerian hormone (AMH) in reproductive-aged women following minimally invasive ovarian cystectomy. A retrospective cohort study was conducted using the medical records of reproductive-aged women who underwent minimally invasive ovarian cystectomy for benign ovarian cysts between January 2018 and December 2022. Data on clinical characteristics, preoperative and postoperative serum AMH levels, operative details, and histopathological results were analyzed. During the study period, 195 patients were included. The mean age of the patients was 32.4 years. All patients underwent minimally invasive surgery, including robotic and laparoscopic ovarian cystectomy. A marked decline of more than 50% in postoperative AMH levels was observed in 28.2% of patients. Univariable logistic regression analysis identified advanced age (≥30 years), endometriosis, bilateral ovarian cysts, adhesiolysis, and prolonged surgical intervention (≥2 hours) as factors associated with a significant postoperative decline in AMH level. Multivariable analysis identified that endometriosis (odds ratio [OR], 3.2; 95% confidence interval [CI]: 1.3–7.9; P = .010) and bilateral ovarian cysts (OR, 2.4; 95% CI: 1.2–5.0; P = .020) were independent predictors of a marked decline in postoperative AMH levels. Advanced age, endometriosis, bilateral ovarian cysts, prolonged surgical intervention, and adhesiolysis were associated with a significant decline in AMH levels following minimally invasive ovarian cystectomy. Among these, endometriosis and bilateral ovarian cysts were independent risk factors for a marked decline of AMH (≥50%).